Inflammatory Burden Index: A Superior Prognostic Biomarker of Systemic Inflammation in Patients on Peritoneal Dialysis - Chen J; Tang R; Tian N; Deng J; Ao S; Peng F; Zhan X; Wen Y; Wang X; Feng X; Su N; Tang X; et al. (Journal of Inflammation Research)
Jiexin Chen,1,* Ruiying Tang,1,* Na Tian,2 Jihong Deng,1 Shuilian Ao,1 Fenfen Peng,3 Xiaojiang Zhan,4 Yueqiang Wen,5 Xiaoyang Wang,6 Xiaoran Feng,7 Ning Su,8 Xingming Tang,9 Xianfeng Wu,10 Qian Zhou,11 Qingdong Xu1 1Department of Nephrology, Jiangmen Central Hospital, Jiangmen, People’s Republic of China; 2Department of Nephrology, General Hospital of Ningxia Medical University, Yinchuan, People’s Republic of China; 3Department of Nephrology, Zhujiang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 4Department of Nephrology, The First Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 5Department of Nephrology, The Second Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 6Department of Nephrology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 7Department of Nephrology, Jiujiang No. 1 People’s Hospital, Jiujiang, People’s Republic of China; 8Department of Hematology, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou, People’s Republic of China; 9Department of Nephrology, Dongguan Songshan Lake Tungwah Hospital, Dongguan, People’s Republic of China; 10Department of Nephrology, Affiliated Sixth People’s Hospital, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 11Department of Medical Statistics, Clinical Trials Unit, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingdong Xu, Department of Nephrology, Jiangmen Central Hospital, No. 23 Hai Bang Road, Jiangmen, 529000, People’s Republic of China, Tel +86 13427226923, Email xqd82@163.comPurpose: Systemic inflammation biomarkers, derived from routine blood tests, have been demonstrated to be associated with prognosis of patients undergoing peritoneal dialysis (PD). However, studies focusing on the comparisons of their role on predictive efficacy for prognosis of PD patient are limited and results are inconsistent. The purpose of this study was to evaluate the prognostic value of various systemic inflammation biomarkers and to identify the optimal one in PD patients.Patients and Methods: This longitudinal study involved 3,225 patients undergoing PD across China. The prognostic accuracy of systemic inflammatory biomarkers was evaluated using C-statistics. Independent prognostic biomarkers of outcomes were determined using multivariate Cox proportional hazards regression analysis.Results: During a 46-month follow-up, 829 (25.7%) patients died, with 458 (55.3%) deaths attributed to cardiovascular disease (CVD). The highest C-statistics were observed for the IBI, with 0.619 and 0.621 for all-cause and CVD mortality, respectively. The optimal threshold of the IBI for predicting prognosis in patients undergoing PD was 50.0. An elevated IBI was a significant independent predictor of all-cause mortality, with a 1-SD increase associated with higher risks of all-cause and CVD mortality. Participants in the upper two quartiles of IBI exhibited increased risks of all-cause mortality by 41.2% and 67.6%, respectively, compared to those in the lowest quartile. Similar results were observed for CVD mortality.Conclusion: The IBI is a superior prognostic indicator of survival and could be broadly applied for prognosis of patients undergoing PD. Elevated IBI is an independent risk factor for all-cause and CVD mortality.Keywords: biomarker, peritoneal dialysis, prognosis, systemic inflammation